Clitic Doubling and Dislocation of Direct Object based on Evidence from Kalhori Kurdish - Sara Ahmadi; Habib Gohari (̒Ilm-i Zabān, 2020)
The present study aimed at investigating clitic doubling in Kalhori Kurdish. The implications of clitic doubling for Kurdish syntax were also investigated. In other words, it was attempted to find whether clitic doubling is a common feature of this language variety or it leads to some syntactic operations including (left or right) dislocation of NP arguments. Another implication of this study is to shed light on the distinction made between (inflectional) affix and clitic. The present study was a descriptive- analytic one in which many arguments were presented to deal with the nature of the relationship between clitic doubling and syntactic structure in Kalhori Kurdish. Theoretically, the present study was mainly based on the Spenser and Luis (2012). Observation, interview and field work were employed to collect the required data. The results indicated that clitic doubling is not a preferred process in Kalhori Kurdish. Instead, Kurdish speakers prefer to dislocate (to right or left) the relevant NP in the sentence to prevent both clitic and its related NP simultaneously.